Time lapsed AVAZ seismic modeling research on CO2 storage monitoring - Wei, Xuwang; Yang, Yang; Ma, Jinfeng (Penerbit Universiti Kebangsaan Malaysia, 2017)
CCUS (Carbon Capture, Utilization and Storage) now is a lead way to reduce greenhouse effect such as carbon dioxide emission in the world. This paper presents an integrated overview of seismic monitoring technology when CO2 injection process. Mainly is time-lapse seismic method .Time-lapse seismic method is a feasible way to monitor CO2 injection process when CO2 interaction with minerals, which is proved an effective method in CCUS experiments. AVAZ (Amplitude versus Azimuth) seismic method is proved a useful tool to indentify CO2 injection process, which can detect fluid-induced seismic anisotropic response and locating where CO2 flow to in reservoirs, therefore, it’s an effective way to monitor CO2 flow in CO2 monitoring process. Since we develop AVAZ modelling experiment base on rock physics theory to modeling the time-lapse AVAZ seismic reservoir response. The research show fluid saturation and pressure behave two main factors influence modeling seismic AVAZ response. Meanwhile the AVAZ response can also be detect by seismic AVAZ data.